Dermoscopic features of pseudoxanthoma elasticum - Aida Oulehri; Zakia Douhi; Sara Elloudi; Hanane Baybay; Fatima Zahra Mernissi (Our Dermatology Online, 2021)
Pseudoxanthoma elasticum (PXE), also known as Gröenblad-Strandberg syndrome, is an autosomal recessive connective tissue disease characterized by aberrant mineralization of soft connective tissue resulting in fragmentation of elastic fibers, involving primarily the skin, eyes and cardiovascular. To our knowledge, there is only two other reports of the dermoscopic features of PXE in the literature. We report clinical and dermoscopic description of two new cases. We hypothesize for the first time that the dermoscopic appearance may differ according to the age of PXE lesions.